Dinamika Self-Censorship dalam Musrenbang: Analisis Faktor dan Dampaknya terhadap Representasi Aspirasi Masyarakat di Kota Surabaya - Alita Aura Zahir; Calista Mutiara Uma; Cendana Anabel; Nabilah Nameera Ruzdy; Ridwan Ridwan; Gema Pertiwi (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The Development Planning Conference (Musrenbang) is a forum for public participation in the preparation of regional development plans. However, discussions on the socio-psychological factors that influence the quality of public participation in Musrenbang remain understudied. This study aims to analyze the phenomenon of self-censorship in the Surabaya City Musrenbang and its impact on the representation of public aspirations. The study used a qualitative approach with a case study design and the self-censorship theory from Bar-Tal (2017). Research data were obtained through a literature review including scientific journals, books, online news, and official government publications. The results show that self-censorship practices are still found in the implementation of Musrenbang due to low confidence in the effectiveness of aspirations, limited understanding of development planning mechanisms, and obstacles in utilizing available participation spaces. These conditions have an impact on the less than optimal representation of public aspirations in the regional development planning process.